DEVELOPMENT OF COMIC-BASED LIVE WORKSHEET STUDENT WORKSHEETS TO IMPROVE LEARNING OUTCOME OF SOLAR - Ika Fadhilla; Ajat Sudrajat (ISER (Indonesian Science Education Research), 2023)
One of the uses of technology in education is to use e-learning-based learning media. E-learning media is a learning media equipped with web access. E-learning can make it easier for teachers to access various materials, worksheets and teaching materials through various media, one of which is by using Live Worksheets. The cause of low learning achievement is that students are less creative in learning, lack of practice questions and less interesting questions. Based on this, learning media is needed that can support the teaching process through comic-based student worksheets. The development of comic-based student worksheets aims to determine the validity of the media, students' responses to the media, and the effectiveness of the media developed in improving student learning outcomes. The method used in media development is ADDIE. Data collection techniques used in this study include: interviews, questionnaires or questionnaires and test techniques. The data analysis in this study is descriptive analysis and N-gain test. The sample used in this study is one lecturer who is a material expert, design expert, media expert, and 30 seventh grade students at the state junior high school 24 Medan. The validation results obtained from material experts, design experts, media experts are feasible to use. The responses obtained from students are also very good and learning media can improve student learning outcomes, it can be seen from the N-gain test calculation score, which is 0.71 in the high category